Balenciaga - Descalzo, Amalia (New York, NY : Thames & Hudson, 2012)
Cristobal Balenciaga made his name in Paris in the 1940s and 1950s in the golden age of haute couture, and was hailed by Coco Chanel as the only true couturier amongst us, able to design, cut, assemble and sew a dress entirely by himself. This book intends to mark the inauguration of the Balenciaga Museum in Getaria, Guipuzcoa, Spain.
boek
Keywords: Balenciaga